Comparison of Erosion Monitoring Methods in the Pisha Sandstone Areas of the Chinese Loess Plateau Based on UAV-SfM Data - LIU Yilin; LI Pengfei; LI Dou; HU Jinfei; BAI Xiao; YAN Lu; DAN Yang (Shuitu Baochi Xuebao, 2024)
[Objective] To compare the applicability of terrain change monitoring algorithms in the pisha sandstone areas of the loess plateau. [Methods] A branch gully Telagouagou Huangfuchuan was taken as the research object, including digital elevation model of difference (DoD), cloud to cloud (C2C), cloud to mesh (C2M), and multiscale model to model cloud comparison (M3C2). Point cloud data employed to operate the four algorithms were produced using the SfM technique based on images acquired by UAV between July 2022 and March 2023. The impact of point density changes in the accuracy of the employed algorithms was also investigated. [Results] (1) All four algorithms were capable of effectively monitoring large surface changes. Among them, the M3C2 algorithm performed the best with the highest accuracy (R2=0.953, p<0.01) and the lowest error (MAE=0.016 1 m, MRE=3.37%, RMSE=0.019 4 m), followed by the C2M algorithm, DoD algorithm, and C2C algorithm. (2) The DoD algorithm was only suitable for flat areas and yielded overestimated results for steep sloping areas. (3) The M3C2 and C2C algorithms were sensitive to point cloud density, while the C2M and DoD algorithms were less sensitive. [Conclusion] The study provided a useful reference for the selection of erosion monitoring methods for the Pisha sandstone areas.